Implementation Of Group Guidance Using Peer Group Technique To Increase Students - Ardika, Gini Widia; I, Sunaryo A.; Apriatama, Dony (Syams, 2022)
This research was conducted at Isen Mulang Palangka Raya senior high school using a sample of 8 students with the aim of knowing how to apply group guidance with peer group technique to increase students